The Influence of Situational Leadership Style, Emotional Intelligence, and Work Discipline on Employee Performance at The Bangkalan Pratama KPP - Zukhrizal Irbani; Kuswandi; Sri Rahayu; Rifda Fitrianty (International Publisher, 2025)
This study examines the influence between situational leadership style, emotional intelligence, and work discipline on employee performance at KPP Pratama Bangkalan. The sample in this study were 77 employees at the Bangkalan Primary Tax Service Office. In writing this thesis, the author uses primary data collection techniques, which are obtained by distributing Likert scale questionnaires. The results showed that partially the variables of situational leadership style, emotional intelligence, and work discipline had a significant effect on employee performance, at the Bangkalan Primary Tax Service Office simultaneously the variables of situational leadership style, emotional intelligence, and work discipline had an effect on employee performance, at the Bangkalan Primary Tax Service Office.